Effect of amorphous microphase on structural evolution of polypropylene membrane at hot stretching - Ming Xie; Licheng Wang; Hao Li; Liuxiang Zhan; Mingyuan Li; Zhengguo Cai; Junfen Sun; Long Chen (Polymer Testing)
This work is aimed at researching the effect of amorphous microphase on structural evolution of polypropylene (PP) membrane at hot stretching. Herein, the functioned copolymer PPO(nPe)0.75-(Py)0.25 (PPOR) was synthesized to introduce the amorphous microphase, enriched region formed by physical crosslink, in PP/PPOR membrane by melt-stretching. The aggregated structure evolution led to the structure and performance modification of blending membrane. First, the amorphous microphase resulted in the amorphous thickness of the PP/PPOR film decreasing by 26.7 %. During the hot stretching process, the micropore formation was accompanied by a decrease of crystal length and an increase of amorphous orientation in the PP membrane. However, the presence of amorphous microphase reduced crystal destruction and amorphous orientation in the PP/PPOR membrane, which contributes to a greater region of micropore and a smaller pore size. Eventually, compared with pure PP membrane, the porosity of PP/PPOR membrane increased by 21.7 % at maximum and the lithium-ion conductivity of the PP/PPOR-10 membrane was enhanced by 13.0 %. This work provides a practical way from molecular design to separator design.